David Maydole Matteson papers - Matteson, David Maydole, 1871-1949.
Correspondence (1907-1935); research notes and card files on riots in the United States from 1641 to 1894 including those involving Nathaniel Bacon, John Brown, Jacob Leisler, Daniel Shays, and Nat Turner; writings on Chinese immigration and the constitutional basis for direct taxation; and material relating to a dinner honoring Albert Bushnell Hart.
Historian and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bacon, Nathaniel, -- 1648-1676.; Brown, John, -- 1800-1859.; Hart, Albert Bushnell, -- 1854-1943.; Leisler, Jacob, -- -1691.; Shays, Daniel, -- 1747-1825.; Turner, Nat, -- 1800?-1831.; Bacon's Rebellion, 1676.; Constitutional law; Direct taxation -- Law and legislation -- United States; Riots; Shays' Rebellion, 1786-1787.; Southampton Insurrection, 1831.; China -- Emigration and immigration; Harpers Ferry (W. Va.) -- History -- John Brown's Raid, 1859.; United States -- History -- Sources; Educators; Historians